Knowledge, Attitude, and Practices (KAP) about Sexual Harassment at Workplace: A Roadmap for Sustainable Workplaces - Gautam, Upma; Bajpai Tewari, Deeksha (European Journal of Sustainable Development, 2021)
Globalization, its corollaries -increased female literacy levels and rapid urbanization, has brought a radical change in women worldwide. However, with the more significant influx of women in India's mainstream workforce, sexual harassment at the workplace has assumed more critical dimensions. Assessment of the awareness, attitudes, and perception of colleagues towards the victim, victimization, and the wrongdoer through a KAP research methodology which is meant to be a representative survey of a target population, forms the central focus of the study. The sample size was 512 respondents from public and private sector undertakings. The structured questionnaire consisted of four core sections ranging from including respondent’s socio-demographic characteristics to including questions regarding the assessment of respondents' knowledge of sexual harassment at the workplace and committee to address the issue, their attitudes towards sexual harassment at the workplace, and inquiries about practice towards sexual harassment at workplace. The study affirms, firstly, both public and private sector organizations lack in their rehabilitative approach towards the victim. Secondly, the co-workers' approach both in the private and public sector lacks sensitivity and includes victim-blaming. Thirdly, there is a need for sensitization training of ICC members. Building Safe workplaces is a prerequisite to building sustainable workplaces.